2020
DOI: 10.3389/fmicb.2020.01563
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase-Producing Klebsiella pneumoniae From Transplanted Patients in Brazil: Phylogeny, Resistome, Virulome and Mobile Genetic Elements Harboring blaKPC–2 or blaNDM–1

Abstract: Objectives Carbapenemase-producing Klebsiella pneumoniae (CP-Kp) is a major cause of infections in transplanted patients and has been associated with high mortality rates in this group. There is a lack of information about the Brazilian structure population of CP-Kp isolated from transplanted patients. By whole-genome sequencing (WGS), we analyzed phylogeny, resistome, virulome of CP-Kp isolates, and the structure of plasmids encoding bla KPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 72 publications
2
22
0
6
Order By: Relevance
“…. But Raro et al found out only nine isolates (11.2%) out of 80 isolates collected carrying blaNDM-1[26]. While Devkota et al reported 30% frequency of blaNDM-1 carrying isolates in a study done in Nepal[27].…”
mentioning
confidence: 96%
“…. But Raro et al found out only nine isolates (11.2%) out of 80 isolates collected carrying blaNDM-1[26]. While Devkota et al reported 30% frequency of blaNDM-1 carrying isolates in a study done in Nepal[27].…”
mentioning
confidence: 96%
“…Here, the diversity and abundance of Inc groups found in K. pneumoniae strains contrast with P. aeruginosa and A. baumannii results. The majority of K. pneumoniae strains analyzed have the IncFIB plasmid, a group known for their MDR characteristic ( 39 , 40 ). In Brazil, the IncFIB plasmid has already been described as carrying bla KPC−2 and bla NDM−1 in K. pneumoniae ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of K. pneumoniae strains analyzed have the IncFIB plasmid, a group known for their MDR characteristic ( 39 , 40 ). In Brazil, the IncFIB plasmid has already been described as carrying bla KPC−2 and bla NDM−1 in K. pneumoniae ( 40 , 41 ). A recent manuscript reported that plasmids with IncR, ColRNAI and IncF co-exists in KPC-2-producing K. pneumoniae strains from ST11 ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of K. pneumoniae strains have the IncFIB plasmid, a group known for their multi-drug resistance. In Brazil, the IncFIB plasmid has been described as a carrier of bla KPC in K. pneumoniae [27]. The spread of bla KPC is related to dispersion of Tn4401 transposon, carried by IncN plasmids mainly disseminated by the clonal complex [28].…”
Section: Discussionmentioning
confidence: 99%